MiR-192 suppresses T follicular helper cell differentiation by targeting CXCR5 in childhood asthma. (3rd April 2018) - Zhang, Defeng; Wu, Yuanbo; Sun, Gengyun
Abstract: The aim of this study was to investigate the role of miR-192 in differentiation of T follicular helper cells in childhood asthma. Blood samples were taken from eighteen children with acute asthma attacks and fifteen healthy children (HC). Quantitative real-time PCR and Western blotting were used to detect the expression levels of miR-192, C-X-C chemokine receptor type 5 (CXCR5), B-cell lymphoma 6 (BCL-6) and inducible T-cell costimulator (ICOS). The flow cytometry was performed to detect the proportion of CD4 + CXCR5+ Tfh cells on CD4 + T lymphocytes. The enzyme-linked immunosorbent assay (ELISA) was carried out to determine the plasma concentrations of total IgE and IL-21. The effect of miR-192 on the T follicular helper cells differentiation by targeting CXCR5 was determined by dual-luciferase reporter assay. Children with asthma had lower levels of miR-192 than HC. The proportion of CD4 + CXCR + Tfh cells was significantly higher in the acute asthma group than HC. Similarly, the plasma concentration of total IgE and IL-21 in the acute group markedly increased compared with the HC, and IgE concentration was positively correlated with the proportion of CD4 + CXCR5 + Tfh cells. Furthermore, the expression levels of CXCR5, Bcl-6 and ICOS were significantly higher in the acute group than in the HC. While the proportion of CD4 + CXCR5 + Tfh cells, IL-21, CXCR5, Bcl-6 and ICOS were obviously lower in the CD4 + T cells transfected with miR-192 plasmid than that in miR-192 + CXCR5 group and control group. In conclusion, miR-192 blocks the activation pathway of Tfh cells by targeting CXCR5, which is a reasonable cellular target for therapeutic intervention.